Kearifan Lokal Marsiadapari: Refleksi Ekologis Dalam Marhobas Pada Pesta Batak - Trivena Br Nadeak (Jurnal Magistra, 2024)
Mutual cooperation is also a local wisdom of the Toba Batak community, which is often referred to as Marsiadapari, a mutual cooperation activity carried out by the Toba Batak community in providing labor assistance without giving wages to the people who help them. Marsiadapari is carried out voluntarily to help each other in the community around their rice fields who need help. The aim of the research is to find out the local wisdom of Marsiadapari carried out in Marhobas at Batak Feasts and to find out the Modernization of Marsiadapari: Ecological Reflections in Marhobas at Batak Feasts. The method used in this research is a qualitative method based on case studies and literature studies and uses reliable and accurate sources such as journals, books and the Bible. Marsiadapari: ecological reflection in marhobas at Batak festivals is local wisdom that has long existed, but with the rapid modernization that is creating many changes, Toba Batak people need to be more critical in responding to current modernization, not to turn a blind eye to the modernization of local wisdom of the Batak community Toba, and can also maintain the ecology of Marhobas at the Toba Batak party.